Prevalence of Conventional Risk Factors in Acute Coronary Syndrome Patients in Eastern Part of Nepal - Rajesh Nepal; Madhav Bista; Abdul Khaliq Monib; Manoj Kumar Choudhary; Aakriti Bhattarai (Journal of Nobel Medical College, 2017)
Background: Smoking, diabetes mellitus, hypertension and dyslipidemia are known as conventional risk factors of coronary artery disease (CAD) and the prevalence of it varies across populations. There is paucity of data in our country about the prevalence of risk factors for acute coronary syndrome (ACS). This study aims to assess the prevalence of these conventional risk factors in patients who were admitted in Nobel medical college, with the diagnosis of ACS.